Toxicity of cadmium and zinc to small soil protists. (November 2018) - Johansen, Jesper Liengaard; Rønn, Regin; Ekelund, Flemming
Abstract: Small heterotrophic protists (flagellates and naked amoebae) are very abundant in soil and play a key role in maintaining soil services. Hence, knowledge on how xenobiotics affect these organisms is essential in ecosystem management. Cadmium (Cd) is an increasing environmental issue as both industrial deposition and recycling of heavy metal rich waste products have led to Cd enrichment of soils. Evaluation of toxicity of Cd to micro-organisms is often performed using a solution of pure Cd (e.g. CdCl) in liquid culture. This approach may be highly misleading as interactions between Cd and other substances, e.g. various ions or inherent soil components often strongly modify Cd toxicity. Hence, we compared the toxic effect of Cd to small heterotrophic protists in soil microcosms and liquid culture. We also evaluated how zinc (Zn) affects Cd toxicity, as Zn usually accompanies Cd in a ratio of c. 100:1, and is known to impede Cd toxicity. In the soil microcosms, we also monitored the primary food source of the protists, i.e. culturable bacteria, and used soil respiration as a proxy of soil functioning. Finally, we examined to what extent Cd actually sorbs to soil. We found 1) that c. 10 3 times more Cd was required to obtain the same effect in the soil microcosms compared to the liquid culture, 2) that soil sorption explains why Cd, even though highly toxic in aqueous solutions, has very limited effect when applied to soil, and 3) (very surprisingly) that in our experimental systems Zn was as toxic as Cd. Our study suggests that Cd toxicity to soil protists will be small because most Cd in soil will be sorbed to the soil matrix and because the Zn:Cd ratio of 100:1 in most substances, incl. pollutants, will mean that lethal Zn effects will occur before Cd reaches toxic levels. Graphical abstract: Image 1 Highlights: We examined cadmium and zinc toxicity to small protist in an aqueous and a soil system. Sorption processes decreased cadmium and zinc bioavailability in the soil system. 10 3 times more Cd was required to obtain the same effect in the soil system compared to the aqueous system. Surprisingly, cadmium and zinc appears equally toxic even though zinc is an essential micro-nutrient. Under normal circumstances zinc will affect the environment before cd, because it is 100 times more abundant.